Lecturers' understanding and teaching practices in embedding soft skills into compulsory courses - Maharoff, Marina; Hassan, Aminuddin (International Organization Center of Academic Research, 2015)
Since Vision 2020 has been established in 1991, the paradigm in education system in Malaysia has been shifted from teaching to learning. Teaching paradigm is synonym with teacher-centered learning while learning paradigm is for student-centered learning. Starting from the year 2006, Ministry of Education Malaysia (KPM) has obligated the implementation of soft skills in Higher Education Institution (HEI) while Institute of Teacher Education (IPG) has taken their initiative by embedding soft skills into the teaching and learning of compulsory courses in Degree of Teaching Programme (PISMP). Soft skills embedding into the teaching and learning of compulsory courses has raised issues that can address both the challenge to teach compulsory courses and at the same time to embed soft skills as prescribed by IPG. This study was undertaken to obtain answers for the research questions; (i) What are the lecturers’ belief in the teaching of compulsory courses in embedding soft skills at IPG? and (ii) How the lecturers practicing the teaching of compulsory courses in embedding soft skills at IPG? The study used the case study methodology through a qualitative approach. Respondents were five lecturers with different backgrounds and teaching experience. Data were collected through several methods; (i) individual interviews; (ii) the observation in the classroom; (iii) stimulated recall interviews; and (iv) document analysis. The findings resulted in improved understanding on lecturers' understanding about soft skills embedment and how the actual process of embedding soft skills occurred. The results of this study allow those involved in the development of student-teachers soft skills to generate ideas to develop models for soft skills embedment that are in line with the interpretation of PISMP soft skills.